MICROSTRUCTURAL CHARACTERISTICS OF IRIDO-CORNEAL ANGLE OF THE EYE OF RATS UNDER THE INFLUENCE OF OPIOID - Yakymiv, N.Y.; Kryvko, Y.Y. (World of Medicine and Biology, 2013)
Based on the complex morphological research, we established morphological features in the structure of irido-corneal angle in rats at different stages of chronic opioid exposure. And it is proved that the severity of these changes depends on the duration of administration of opioid analgesics and is shown primarily by the microvasculature of the investigated area.